2008
DOI: 10.14411/eje.2008.033
|View full text |Cite
|
Sign up to set email alerts
|

Plant architecture and vegetation structure: Two ways for insect herbivores to escape parasitism

Abstract: Abstract.Interactions between herbivorous insects and their parasitoids occur in highly structured and complex environments. Habitat structure can be an important factor affecting ecological interactions between different trophic levels. In this study the influence of plant architecture and surrounding vegetation structure on the interaction between the tansy leaf beetle, Galeruca tanaceti L. (Coleoptera: Chrysomelidae) and its egg parasitoid, Oomyzus galerucivorus Hedqvist (Hymenoptera: Eulophidae), was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 55 publications
1
66
0
5
Order By: Relevance
“…For example, although it is widely accepted that many birds enhance their flight capacities by making use of predictable sources of rising air [5] and that terrestrial animals expend more energy moving over soft substrate than hard [6], general consideration of the energetic costs of animals moving through their variable landscapes is minimal (but see [7]). Landscapes vary in character in both space and time with, for example, heterogeneous vegetation landscapes changing during succession [8,9] and over the growing season [10], becoming correspondingly more problematic for animals to move through [11]. Indeed, the degree of variation in the landscape (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although it is widely accepted that many birds enhance their flight capacities by making use of predictable sources of rising air [5] and that terrestrial animals expend more energy moving over soft substrate than hard [6], general consideration of the energetic costs of animals moving through their variable landscapes is minimal (but see [7]). Landscapes vary in character in both space and time with, for example, heterogeneous vegetation landscapes changing during succession [8,9] and over the growing season [10], becoming correspondingly more problematic for animals to move through [11]. Indeed, the degree of variation in the landscape (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, interactions between arthropod predators seem to be more strongly affected by structure than the consumption of prey from a different trophic level (Roda et al 2000;Finke and Denno 2002;Obermaier et al 2008). A recent metaanalysis concluded that habitat structure should promote persistence of predators by reducing intraguild predation (Janssen et al 2007), which can have important impacts on herbivore control (Finke and Denno 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Langelotto & Denno, 2004;Crist et al, 2006;Obermaier et al, 2008;Randlkofer et al, 2009). In terrestrial systems density, height and fragmentation of the vegetation seem to be the most important at the habitat level and at the individual plant level it is mainly plant height that has a strong positive influence on herbivore distribution and oviposition (Crist et al, 2006;Obermaier et al, 2008;Randlkofer et Fig. 6.…”
Section: Discussionmentioning
confidence: 99%